Community participation in social movements: the case of the Landless People's Movement in Thembelihle, Johannesburg - Nyawade, Steva (My University, 2016)
The emphasis in making government more accessible to the people has produced dismal effects, this has led to the emergence of civil society organizations claiming to give the voiceless a voice and facilitating participation of the marginalized towards how they are governed. This research, through a case study of the Landless People’s Movement in Thembelihle (LPM – Thembelihle) focuses on the internal dynamics of a community’s participation in social movements. The study questions social movements’ efforts in nurturing participation within them and whether the assumed claims of representation are reflective to the participants needs. The report argues that social movements do not necessarily nurture democratic principles such as participation within them. The reasons for this are: 1) social movements have been engineered to focus on the state as the adversary thus their efforts are outward looking 2) the nature of the issues they tackle are highly politicized and thus attract a large following regardless. Analyzing data from interviews and various documents, first and foremost the study aimed to investigate the level of participation by the community in LPM - Thembelihle using the concept and typologies of participation as stipulated in the ladder of participation. Secondly, the aim was to connect the level of participation to the representation of the participating community in an attempt to find if at all there is a correlation. The findings revealed that in spite of community control of the LPM –Thembelihle branch, a deep degree of participation was not achieved but that did not deter LPM’s representation of the Thembelihle community. As this may be a contradiction regarding the empowering aspects of participation, the study concludes by suggesting that community participation should also be used to enrich social movement organizations considering their structured nature and role as intermediaries
A research report submitted to the School of Social Sciences, Faculty of Humanities of the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Masters of Arts in Development Studies March, 2016
Keywords: Local government--South Africa--Citizen participation; Community organization--South Africa--Johannesburg; Social movements--South Africa--Johannesburg; Political participation--South Africa--Johannesburg